Osteoinductive properties of the bone marrow Myth or reality - Tshamala, M.; van Bree, H. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
The osteogenic potential of red bone marrow was first reported more than 100 years ago. Since then, studies have reported controversial results that do not confirm nor disprove the capacity of fresh red bone marrow to produce bone. Researches have been focused on techniques that improve the efficiency of the bone marrow, including: the increase of the concentration of the mesenchymal stem cells in the aspirated bone marrow, the combination with a ‘carrier’ that helps to maintain the mesenchymal stem cells and guides and supports the vascular ingrowth in the defect, or the combination with bone growth factors that stimulate the marrow stromal cells to differentiate into bone forming cells. Each of these techniques has its drawbacks and increases the expenses of an operation. On the other hand, the synergistic effect observed with these combinations does not resolve the problem of the osteogenic capacity of pure bone marrow, which still remains questionable.
Keywords: Bone marrow; osteogenesis; osteoinduction; ceramics; growth factors